A living WHO guideline on drugs for covid-19. (4th September 2020) - Rochwerg, Bram; Siemieniuk, Reed AC; Agoritsas, Thomas; Lamontagne, François; Askie, Lisa; Lytvyn, Lyubov; Agarwal, Arnav; Leo, Yee-Sin; Macdonald, Helen; Zeng, Linan; Amin, Wagdy; Burhan, Erlina; et al.
Abstract: Clinical question: What is the role of drug interventions in the treatment of patients with covid-19? New recommendation: Increased attention on ivermectin as a potential treatment for covid-19 triggered this recommendation. The panel made a recommendation against ivermectin in patients with covid-19 regardless of disease severity, except in the context of a clinical trial. Prior recommendations: ( a ) a strong recommendation against the use of hydroxychloroquine in patients with covid-19, regardless of disease severity; (b) a strong recommendation against the use of lopinavir-ritonavir in patients with covid-19, regardless of disease severity; (c) a strong recommendation for systemic corticosteroids in patients with severe and critical covid-19; ( d ) a conditional recommendation against systemic corticosteroids in patients with non-severe covid-19, and ( e ) a conditional recommendation against remdesivir in hospitalised patients with covid-19. How this guideline was created: This living guideline is from the World Health Organization (WHO) and provides up to date covid-19 guidance to inform policy and practice worldwide. Magic Evidence Ecosystem Foundation (MAGIC) provided methodological support. A living systematic review with network analysis informed the recommendations. An international guideline development group (GDG) of content experts, clinicians, patients, an ethicist and methodologists produced recommendations following standards for trustworthy guideline development using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Understanding the new recommendation: There is insufficient evidence to be clear to what extent, if any, ivermectin is helpful or harmful in treating covid-19. There was a large degree of uncertainty in the evidence about ivermectin on mortality, need for mechanical ventilation, need for hospital admission, time to clinical improvement, and other patient-important outcomes. There is potential for harm with an increased risk of adverse events leading to study drug discontinuation. Applying pre-determined values and preferences, the panel inferred that almost all well informed patients would want to receive ivermectin only in the context of a randomised trial, given that the evidence left a very high degree of uncertainty on important effects. Updates: This is a living guideline. It replaces earlier versions (4 September, 20 November, and 17 December 2020) and supersedes the BMJ Rapid Recommendations on remdesivir published on 2 July 2020. The previous versions can be found as data supplements. New recommendations will be published as updates to this guideline. Readers note: This is the fourth version (update 3) of the living guideline ( BMJ 2020;370:m3379). When citing this article, please consider adding the update number and date of access for clarity.